Comparing laser desorption/Laser ionization mass spectra of asphaltenes and model compounds - Sabbah, Hassan; Morrow, Amy L.; Pomerantz, Andrew E.; Mullins, Oliver C.; Tan, Xiaoli; Gray, Murray R.; Azyat, Khalid; Tykwinski, Rik; Zare, Richard N. (Energy & Fuels, 2010)
The molecular-mass distribution of the asphaltene fraction of petroleum is rapidly becoming more constrained, but the molecular architecture remains poorly understood. Two types of molecular structures have been proposed to be representative of asphaltenes: the "island" model and the "archipelago" model. Here, nine compounds were synthesized on the basis of pyrene, representing both types of models. These compounds were analyzed using two-step laser desorption/laser ionization mass spectrometry (LMS), and the compounds were classified into three groups based on their fragmentation behavior in this typically soft ionization technique. The first two groups, denoted "highly fragmented" and "variably fragmented", include eight of the nine studied compounds. The masses of fragment ions from the "highly fragmented" group were too small for these specific compounds to dominate the asphaltenes. The fragmentation behavior of the variably fragmented group was inconsistent with LMS spectra of asphaltene samples; thus, these specific compounds can be excluded from being dominant in asphaltenes. The third group, "highly stable", contains a single model compound with properties in the aromatics class fraction and exhibits a behavior consistent with previously observed asphaltene samples, namely, inappreciable fragmentation as a function of laser pulse energy used. Although suggestive, no definitive conclusion can be reached as to the dominant molecular architecture of asphaltenes without the study of how more model compounds behave under LMS. © 2010 American Chemical Society.